Rescue of Fatal Neonatal Hemorrhage in Factor V Deficient Mice by Low Level Transgene Expression - Yang, Tony L.; Cui, Jisong; Taylor, Jeremy M.; Yang, Angela; Gruber, Stephen B.; Ginsburg, David (Thrombosis and Haemostasis, 2000)
Factor V (FV) is a critical component of the coagulation cascade. FV-deficient patients suffer moderate to severe bleeding, though residual FV activity is detectable in nearly all cases. In contrast, FVdeficient mice die either during mid-embryogenesis, or of massive perinatal hemorrhage. In order to examine the requirements for FV in murine embryogenesis and hemostasis, we generated transgenic mouse lines expressing a Fv minigene under control of either the tissue-specific albumin (Malb) or rat platelet factor 4 (Rpf4) promoter. A total of 12 Malb and 3 Rpf4 lines were analyzed. Though expression in the target tissue was detectable in most lines by RT-PCR, only low levels of transgene expression were achieved (<3% of endogenous Fv in all lines). Despite a low level of Fv transgene expression, rescue of the lethal Fv−/− phenotype was observed with one of the Malb transgenic (Tg+) lines. However, rescue appeared to be incomplete with continued loss of >1/2 of expected Tg+, Fv−/− mice in early embryogenesis. Rescued Tg+, Fv−/− mice have undetectable FV (<0.1%) in both plasma and platelet compartments, but survive the perinatal period and mature to adulthood without spontaneous hemorrhage. We conclude that FV present at <0.1% is sufficient to support postnatal survival. Failure of the Malb transgene to rescue the midembryonic block suggests that FV expression is required during mammalian development at higher levels or with a different tissue-specific or temporal pattern. Taken together, these data may explain the observation of residual FV activity in most human FV-deficient patients due to early embryonic lethality in those absolutely deficient, and suggest that minimal levels of FV expression, below the level of detection, also may be sufficient to support survival in humans.
Keywords: Transgenic; mice; factor V